Ethnic culture, religion, and the mental health of Slavic-American women - Krause, Corinne Azen (Journal of religion and health, 1979)
Findings of a comparative research study of women of different ethnic back-grounds suggest that the Slavic religioethnic culture acts to promote successful aging and stable mental health among women of Slavic heritage. Home and family structure, deep religiosity, and participation in church and community affiars provide function and meaningful purpose to life that tends to mitigate the losses inherent in the aging process.